Hexagonal CSRR Etched Rectangular Microstrip Patch Antenna for Triband Application - Kavitha. A and Deepa. J (International Journal of Advanced Science and Technology, 2020)
In this paper, a hexagonal complementary split ring resonator inspired rectangular patch antenna is proposed for tri band application. The entire structure is feed with 50-ohm microstrip feed. The entire structure is fabricated on a FR4 substrate wit defected ground structure. The total size of the proposed antenna is 23 mm x 21 mm x 1.6 mm. The operating band of the proposed antenna is 2.99 GHz to 3.54 GHz, 3.72 GHz to 5.96 GHz and from 6.16 GHz to 8.84GHz which covers the all the wireless communication technologies such as WLAN, WIMAX and Satellite communication respectively. The proposed antenna has a very good choice for the all the application and it is proved with the simulated results of Return loss, VSWR, Surface current, Gain and the Radiation patterns.